QUALITY CONTROL OF THE COSTA RICAN CADASTRAL MAP USING OPEN SOURCE GEOGRAPHIC INFORMATION SYSTEMS (GIS) - Ramírez-Núñez, Manuel; Mora-Vargas, Esteban A. (Revista Geográfica de América Central., 2015)
This article presents a methodology for quality control of the cadastral map based on the tools provided by Open Source Geographic Information Systems (GIS). Errors in the cadastral map have a direct impact on information systems that may lead to wrong decision-making, increase cost of maintenance and updating of the spatial data. The developed methodology was used and validated by the Costa Rican Cadastre and Register Regularization Program. As a product of this program, a continuous cadastral map of Costa Rica was created to be used for the cadastral and registry transactions within the National Registry. The methodology allows the detection, location and classification of errors in the cadastral map in order to be fixed to ensure that the map is a correct representation of the parcels.